Metamorfismo de alto gradiente P/T en la Sierra de Pie de Palo (Sierras Pampeanas, Argentina): Modelado de equilibrio de fases minerales e implicancias geodinámicas en el antearco famatiniano - Ramacciotti, Carlos Dino (2019)
The Sierra de Pie de Palo (SPP, Western Sierras Pampeanas) shows evidence of two regional metamorphisms: one Mesoproterozoic attributed to the Grenvillian orogeny and other of Ordovician age related to the Famatinian orogeny. The Neoproterozoic-to-Cambrian sedimentary successions that cover the Grenvillian basement only record the Ordovician event. One staurolite-schist from the Ediacaran Difunta Correa Metasedimentary Sequence collected in the southeastern side of the SPP allows to constrain, by means of pseudosections, a prograde evolution from ca. 3 kbar and 515 ºC up to ca. 9 kbar and 640 ºC corresponding to a high P/T gradient. The SPP and the immediately east Loma de Las Chacras outcrop were part of the famatinian forearc which shows a progressive decrease of P (from ca. 13 kbar to 6 kbar), T (from ca. 900 ºC to 450 ºC), and P/T gradient (from ca. 85 ºC/kbar to 35 ºC/kbar) towards the active continental margin on the west. The Caucete Group, in the western side of the SPP, represents the westernmost part of the forearc, near to the active continental margin. Metamorphism was apparently coeval with the Famatinian magmatism and with ductile underthrusting at ca. 470-465 Ma, which led to burial of the forearc beneath the magmatic arc.